Problematika Hukum terhadap Calon Tunggal Kepala Daerah di Kota Samarinda - Muhammad Rahmadian; Insan Tajali Nur; Poppilea Erwinta (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study examines the legal issues of single candidates in the 2024 Samarinda City Regional Elections, focusing on the reasons political parties support single candidates and their impact on the quality of democracy and public participation. The phenomenon of single candidates is viewed as a democratic anomaly because it weakens the essence of political competition. The study uses a non-doctrinal method with primary materials in the form of interviews and legislation, as well as secondary materials from articles and scientific literature. The research results indicate three main factors driving political parties' support for a sole candidate: (1) the high electability of the incumbent, which creates psychological effects and political pragmatism; (2) the nomination threshold provisions that limit the number of potential candidates; and (3) the alignment of party vision and mission with the candidate, making political coalitions easier to form. The implications of this phenomenon affect two aspects. First, the substance of democracy is reduced because the people's choices become limited. Second, public participation may decrease due to the lack of competition, which results in low voter enthusiasm. This study emphasizes the need for more inclusive regulations to ensure healthy local election competition and to support the strengthening of legal and political systems to ensure that the nomination process reflects fairness and the people's aspirations broadly.